Effluent Molecular Analysis Guides Liver Graft Allocation to Clinical Hypothermic Oxygenated Machine Perfusion - Caterina Lonati; Andrea Schlegel; Michele Battistin; Riccardo Merighi; Margherita Carbonaro; Paola Dongiovanni; Patrizia Leonardi; Alberto Zanella; Daniele Dondossola (Biomedicines, 2021)
Hypothermic-oxygenated-machine-perfusion (HOPE) allows assessment/reconditioning of livers procured from high-risk donors before transplantation. Graft referral to HOPE mostly depends on surgeons’ subjective judgment, as objective criteria are still insufficient. We investigated whether analysis of effluent fluids collected upon organ flush during static-cold-storage can improve selection criteria for HOPE utilization. Effluents were analyzed to determine cytolysis enzymes, metabolites, inflammation-related mediators, and damage-associated-molecular-patterns. Molecular profiles were assessed by unsupervised cluster analysis. Differences between “machine perfusion (MP)-yes” vs. “MP-no”; “brain-death (DBD) vs. donation-after-circulatory-death (DCD)”; “early-allograft-dysfunction (EAD)-yes” vs. “EAD-no” groups, as well as correlation between effluent variables and transplantation outcome, were investigated. Livers assigned to HOPE (n = 18) showed a different molecular profile relative to grafts transplanted without this procedure (n = 21, p = 0.021). Increases in the inflammatory mediators PTX3 (p = 0.048), CXCL8/IL-8 (p = 0.017), TNF-α (p = 0.038), and ANGPTL4 (p = 0.010) were observed, whereas the anti-inflammatory cytokine IL-10 was reduced (p = 0.007). Peculiar inflammation, cell death, and coagulation signatures were observed in fluids collected from DCD livers compared to those from DBD grafts. AST (p = 0.034), ALT (p = 0.047), and LDH (p = 0.047) were higher in the “EAD-yes” compared to the “EAD-no” group. Cytolysis markers and hyaluronan correlated with recipient creatinine, AST, and ICU stay. The study demonstrates that effluent molecular analysis can provide directions about the use of HOPE.